Geographical Analysis Of Annual Thermal Ranges Trends In Iraq - Jabbar Al-Khalidy, Hanan; Kadham Alkinani, Nahad Khudhair (Opción, 2019)
The values of annual thermal ranges between stations of the study area wit- ness a spatial variation in their rates and directions, reflecting the effect of the controls affecting the variation of the solar radiation distribution over the region and consequently the thermal range, as their rates ranged between (38.0) m in the Rutba station, and (42.2) m in the station Mosul, all climate stations covered in the study recorded positive trends during the academic period (1988-2017), with the exception of Al-Nukhaib Station, which took a negative direction during the period. It is also noticed that the values of the relative change coefficient (%) between the stations of the study area varied, as the parameter values ranged between (-0.47)% in Al-Nukhaib station, and (5.48)% in Al-Ramadi station, which is what The degree of change in the phe- nomenon during the study years reflects the effect of charting its course dur- ing the study period, and the trend coefficient values varied between stations of the study area, as the coefficient values ranged between (-0.0083) in the Al- Nukhaib station, and (0.1054) in the Ramadi station Also.